An investigation into the cause of loss of containment from the supply of mini-bulk lubricants. (August 2015) - Guerin, Turlough
Highlights: An Intermediate Bulk Container (IBC) was punctured during its handling, releasing oil product. The forklift did not pierce the plastic but rather one of the tynes caught the underside base plate. Projects using IBCs and tyned equipment should manage them to minimize spills from interaction between. Abstract: An Intermediate Bulk Container (IBC) was punctured during its handling, releasing oil onto soil at an environmentally-sensitive region of Australia. The telehandler did not pierce the plastic of the IBC directly (as was expected) but rather one of the tynes had caught on the underside of the metal base plate, despite numerous controls being in place at time of spill, revealing a previously unreported mechanism for a fluid spill from handling of petroleum hydrocarbons. The diverse investigation team used a root cause analysis (RCA) technique to identify the underlying cause: the inspection process was inadequate with contributing factors of not using a spotter and design of IBC did not anticipate conditions. Engineering controls were put in place as part of the change management process to help prevent spills from occurring from piercing from telehandler tynes on the current project site.